The Relationship Between Adolescents' Knowledge Level And Triad Krr Prevention Behaviour (Three Basic Threats To Adolescent Reproductive Health) At Smk Negeri 03 Bengkulu City In 2024 - Sadia, Elva Natur; Rohani, Tuti; Handayani, Tita Septi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Adolescence is a transitional period from childhood to adulthood, during which rapid growth occurs, including reproductive function, thereby influencing changes in physical, mental, and social development. Nearly all adolescent males and females begin their first romantic relationships between the ages of 15 and 17. As a result, 8% of adolescent males and 2% of adolescent females have engaged in premarital sexual intercourse. Additionally, 45.9% of adolescents are living with AIDS, and 51,986 adolescents (approximately 45% of total drug users) are recorded as using illicit drugs. This study aims to determine the relationship between adolescents' knowledge levels and their preventive behaviour regarding the TRIAD KRR among students at SMK N 03 in Bengkulu City. The method used is a quantitative research design employing a descriptive analytical research framework with a cross-sectional approach. The sample was selected using the Slovin formula, resulting in 92 respondents from grades X and XI, selected using Proportionate Stratified Random Sampling. Data were analysed using univariate and bivariate analysis with the Chi-Square test, with a P-value of 0.05. The results of the study indicate that the level of knowledge among adolescents is mostly in the adequate category (58.7%), while most preventive behaviours related to the TRIAD KRR among adolescents are in the inadequate category (60.6%). There is a significant relationship between the level of knowledge among adolescents and preventive behaviours related to the TRIAD KRR, with a P-value of 0.011. The results of this study are expected to serve as an additional source of information, as well as Communication, Information, and Education (KIE) regarding the level of knowledge among adolescents and their preventive behaviour towards TRIAD KRR (Three Basic Threats to Adolescent Reproductive Health) at SMK N 03 Kota Bengkulu in 2024.